Variability among Alternaria porri isolates - M. ANDRABI; T.R. RATHER, EFATH SHAHNAZ*, V.K. RAZDAN (Indian Phytopathology, 2013)
Alternaria porri (Ellis) Cif., the causal agent of purple blotch of onion, incurrs heavy losses in onion production, worldwide. Twenty-six monoconidial isolates of A. porri were collected from the diseased onion leaf and seed stalk samples from different locations in the sub-tropics of Jammu. Differences were recorded among the isolates in their conidial length, width, beak length and number of septa. The average conidial dimensions were 141.28±1.31x22.92±0.14 μm with beak length of 43.61±0.91 μm, 3 to 12 transverse septa and 0 to 5 longitudinal septa. The mycelial characteristics varied on different media from smooth to fluffy and whitish to dark olivaceous. In most of the isolates, zonation was present on carrot potato agar, whereas, on hay extract, mycelia of all the isolates were embedded in the medium. Chlamydospore formation occurred in most of the isolates on potato dextrose agar, onion extract, modified Czapek Dox agar, Brown’s medium and oat meal agar. However, none of the isolates formed chlamydospores on carrot potato agar, Czapek Dox agar, corn meal agar and hay extract. The growth rate per day on potato dextrose agar was maximum in isolate RS-6 and RE-3 (8.23 mm, each) and least (2.08 mm) in G-9. All the isolates could be classified in to three groups viz. fast, moderate or slow growing on the basis of growth rate on PDA.